2018
DOI: 10.1108/et-11-2016-0176
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing the spirit of entrepreneurship in early childhood education through traditional games

Abstract: Purpose The purpose of this paper is to develop entrepreneurship games for early childhood education (ECE) and to develop a module using a number of systematic approaches. Design/methodology/approach There were two studies conducted. Study 1 focused on developing guidelines for traditional games. The games were collected and selected based on their entrepreneurial characteristics. In study 2, the authors selected eight relevant traditional games and then examined their effectiveness at internalizing the spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
0
21
0
3
Order By: Relevance
“…The Indonesian government needs to review its education program. As stated also by Jufri and Wirawan (2018) in their research that the spirit of entrepreneurship can be developed by considering local values, for the example through traditional games even starting from childhood education. Moreover, as studied and found by Rina (2019) there are satisfactory results if the curriculum involve students in activities that are linked to leadership skills.…”
Section: Conclusion and Limitationsmentioning
confidence: 94%
“…The Indonesian government needs to review its education program. As stated also by Jufri and Wirawan (2018) in their research that the spirit of entrepreneurship can be developed by considering local values, for the example through traditional games even starting from childhood education. Moreover, as studied and found by Rina (2019) there are satisfactory results if the curriculum involve students in activities that are linked to leadership skills.…”
Section: Conclusion and Limitationsmentioning
confidence: 94%
“…Some national cultures are influenced by tribal or ancient values. For instance, a number of studies revealed that Eastern Indonesians are nurtured with some degree of Bugis or Buginese values (Jufri and Wirawan, 2018;Tamar et al, 2017). These values are also a part of organisational practices and leverage business performance (Tamar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers and professionals can teach entrepreneurship concepts using role-playing and entertainment games. A card game was used by Jufri & Wirawan (2018) to educate schoolchildren about the importance of fruit and vegetables for well-being and health. The research of (Lohmander and Samuelsson, 2015) offered evidence for the use of games in promoting the process of teaching and learning.…”
Section: The Role Of Play-based Learning For Entrepreneurship Skills mentioning
confidence: 99%